Translation and Validation of the ELPO for Turkish Population: Risk Assessment Scale for the Development of Pressure Injuries Due to Surgical Positioning - Şengül, Tuğba; GÜL, ASİYE; Yılmaz, Dilek; Gökduman, Tuğba (Elsevier, 2022)
Aim of the study: This study was conducted to translate the ELPO risk assessment scale for the development of pressure injuries due to surgical positioning to Turkish and to test its validity and reliability in the Turkish Population. Materials and methods: The data were collected using the patient identification form, the risk assessment scale for the prevention of injuries due to surgical positioning, and the Braden Scale. This scale consisted of a total of seven items, each of which contained five sub-items. It is rated between 1 and 5 in the Likert type. The total score of the scale ranges between 7 and 35. The risk of developing pressure injuries increases in patients as the score increases. Results: A total of 184 patients were included in the study sample. The mean age of the group was 55.96 ± 17.90, and the content validity index was 0.944. The sensitivity of the test was 60%, the specificity was 66%, and the accuracy was 66%. There was a negative, weak, statistically significant correlation between the total scores of the risk assessment scale for the prevention of injuries due to surgical positioning and the Braden scale. The mean total score of the scale was 18.45 ± 2.96 (12-26) and 35.9% (n = 66) of the group were at high risk. Conclusions: The ELPO, which includes the risks specific to patients during surgery, can be used as an assessment scale for the development of pressure injury due to surgical positioning for Turkish population.
Keywords: Elective Surgical Procedure; Pressure Injury; Reliability and Validity; Risk Assessment